To protect and to serve: a history of police in America - Wadman, Robert C. (Pearson/Prentice Hall, 2004)
Police in early America -- The development of municipal policing in the Northeast -- Policing race and violence in the South -- Policing the American West -- Urbanization, progressivism, and police -- The shift to police as profession -- Police and technology -- Leaders in American policing -- Policing to the 21st Century.